RESPON TIGA VARIETAS PADI (Oryza sativa L.) PADA BERBAGAI SISTEM TANAM LEGOWO - Wahyuddin Abbas; Muh Riadi; Ifayanti Ridwan (Universitas Hasanuddin, 2018)
This research was conducted in Village S. Mallori, Sub District Dua Pitue, Sidrap Regencywhich lasted from May to August 2015. This study aims to determine the growth and production ofrice varieties Mekongga, Inpari 14 and Inpari 30 on some legowo planting system. This researchwas conducted based on Split Plot Design. As the main plot is legowo consisting of four croppingsystems, namely tiles (30 cm x 30 cm), legowo 2: 1 (40 cm x 15 cm x 15 cm), Legowo 3: 1 (40 cmx 15 cm x 15 cm), and Legowo 4: 1 (40 cm x 15 cm x 15 cm) while the subplot is a variety consistingof three varieties namely Mekongga, Inpari 14 and Impari 30. There are 12 treatment combinationswhich are replicated 3 (three) times so that overall there are a total of 36 plot total experiments.The results showed that the use of different planting systems significantly significantly affected thegrowth and production of rice crops with the best results shown by tile planting system (30 cm x30 cm) on the parameters of the number of productive tillers of 16.41 stems, the number of grains46per panicle 178.31 grains, and panicle density of 7.02 grains.cm-1. However, the highest yield ofgrain per hectare was shown by the planting of legowo 2: 1 and legowo 3: 1 systems, ie 6.38 and6.33 tons GKP.ha-1, respectively. Inpari 14 varieties gave the best results on the parameters ofnumber of productive tillers (11.22 stems), panicle length (25.99 cm) and percentage of unhulledgrain (85.65%), and empty grain (14.34%). There is no interaction between the treatment ofplanting systems with varieties on the growth and production of good rice crops